Pengaruh Kualitas Pelayanan Terhadap Keputusan Pengambilan Kredit Pelanggan Repeat Order FIFGROUP Cabang Tanjung Pos Buntok - Wahyunawati, Sri; Raissa Helena Momongan (Yayasan Literasi Sains Indonesia, 2022)
A developed economy provides a large selection of goods and services that can be consumed. To meet their needs for goods and services, consumers do not always have to pay in cash because many companies offer financing services. Financing services are specialized in accordance with the development of product diversity and customer needs. Finance service companies must be able to improve the quality of their services to embrace new customers and retain existing customers. This study was made with the aim of knowing and analyzing how the Quality of Service provided by the Spectra Business Unit at FIFGROUP Tanjung Pos Buntok Branch can influence the Decision of Making Consumer Credit RO (Repeat Order). This type of research is a descriptive quantitative type with the data collection process using questionnaires, observations, interviews, library research, and documentation. The selected sample of 124 people determined by the Random Sampling method and then processed by the Multiple Linear Regression method. The results showed that the calculation of multiple linear regression is Y = 4.718 + 1.270X1 + 0.702X2 +0.645X3 + 1.097X4 + 0.656X5. The results of the hypothesis test show that simultaneously service quality has a positive and significant effect on consumer credit decisions at RO FIFGROUP Tanjung Pos Buntok Branch with a calculated F value of 58.402 > F table 2.29. While partially. obtained t count Tangibles (X1) 4.187, Reliability (X2) 2.585, Responsiveness (X3) 2.592, Assurance (X4) 3.739 and Empathy (X5) 2.146, which means that these values ​​are values ​​that greatly affect Credit Decisions by consumers repeat order FIFGROUP Tanjung Pos Buntok Branch because tcount > ttable